A Study of Circular Economy Awareness in University Students: The Assessment of Knowledge, Attitude and Behavior - Didit Herawan; Rahmatika Dewi; Arfani, Junita Widiati (Journal of World Trade Studies, 2022)
This study explores the university students’ awareness of the Circular Economy (CE) through the identification of knowledge, attitudes and behaviors (KAB). A quantitative method is applied by adopting the SDG survey questionnaire of Cifuentes-Faura that was developed using the 5Rs (Reduce, Reuse, Refurbish, Repair and Recycle) of the CE concept to measure the students’ KAB towards CE. A total of 110 students studying economics-related courses from two Indonesian universities participated in the survey and the statistical program SPSS 20.0 was used for data analysis. The study found that the students’ awareness of the circular economy is higher in terms of knowledge (85.5%) than attitude (55.5%) and behavior (68.2%). In a way, the results of attitude and behavior show that students tend to buy new things instead of reusing/renting or repairing them. The female students' knowledge of CE is higher than male students, whereas their attitude and behaviour show similar results. Additionally, there is a correlation between knowledge and attitude, attitude and behavior, and knowledge and behavior, which means that the variables influence each other.